Raised troponin T and echocardiographic abnormalities after prolonged strenuous exercise—the Australian Ironman Triathlon. Issue 7 (12th April 2006) - Tulloh, L; Robinson, D; Patel, A; Ware, A; Prendergast, C; Sullivan, D; Pressley, L
Abstract : Background: There is concern about whether cardiac damage occurs as a result of prolonged strenuous exercise. Objective: To investigate whether competing in a triathlon is associated with cardiac damage based on a sustained increase in cardiac troponin T (cTnT), and whether such an increase correlates with echocardiographic changes Methods: cTnT and echocardiographic measurements were made in 38 participants in the 2001 Australian ironman triathlon. cTnT was measured the day before, immediately after, and the day following the race. Echocardiography was done the day before, immediately after, and two to six weeks later for measurement of ejection fraction, stroke volume, cardiac output, wall motion analysis, and global left ventricular function (LVF). Results: No subject had detectable cTnT in the pre-race sample. Following the race, 32 subjects (86.5%) had detectable levels of cTnT (>0.01 ng/ml), with six (16.2%) having >0.10 ng/ml. The day after the race, nine subjects (23.7%) still had detectable cTnT, with two recording a level >0.10 ng/ml. Previously described echocardiographic changes of "cardiac fatigue" were observed in the whole cohort. There was a modest but significant correlation between change in ejection fraction and peak cTnT level (p = 0.02, r  = 0.39). Athletes with a post-race cTnT >0.10 ng/ml had a greater decrease in global LVF (p = 0.02) and a trend toward a greater fall in ejection fraction and stroke volume than athletes with cTnT levels <0.10 ng/ml. Cardiac output fell in the group with cTnT >0.10 ng/ml (p>0.05). Conclusions: Participation in ironman triathlon often resulted in persistently raised cTnT levels, and the troponin rise was associated with echocardiographic evidence of abnormal left ventricular function. The clinical significance and long term sequelae of such damage remains to be determined.